PENINGKATAN PERAN KOHESI DAN SOLIDARITAS SOSIAL PETANI MEDUKUNG KEBERHASILAN PENYALURAN JARING PENGAMAN SOSIAL DI MASA PANDEMI COVID19 - Roosganda Elizabeth (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The Covid19 pandemic outbreak, which is fast and widespread, has spread throughout the world and is still ongoing, greatly affecting the economy of people and life in all countries. The impact on the socio-economic life of society and the country, including increased unemployment and economic hardship. The absence of income due to disconnection / loss of livelihood sources to meet food and clothing needs is an important pillar. Apart from the economic and health sectors, it also affects the agricultural sector and related to it. This paper aims to present the active role of the government in overcoming economic difficulties and the agricultural sector through the distribution of the Social Safety Net (SSN/JPS) assistance program which is more targeted, the type of assistance and the timing of its receipt. With the qualitative descriptive method, a review of various information, literature and results of studies related to the distribution of JPS especially to small farmers during the Covid 19 pandemic is described. Various situations and conditions in society and the world tend to reflect panic not only in health, but also extending to the economic structure food security and social life which require more serious handling. The Covid-19 pandemic is a momentum that has brought various broad and multi-dimensional impacts, where normal mechanisms that rely on market mechanisms are difficult to recover. The need to empower and increase social cohesion and solidarity which are very important in maintaining cohesion between citizens and being a means of social control, accompanied by the values of altruism that have grown and developed in society must be revived as social solidarity that can strengthen social cohesion. The JPS program is a necessity that must be carried out by the government, even though it is accompanied by interventions in the smooth implementation of its distribution.